SISTEM NOTIFIKASI SWITCH BERBASIS TEKNOLOGI WIRELESS - Jessica Indrayani, Janice; Nyoman Pramaita, Nyoman Pramaita; Oka Widyantara, I Made (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p22, 2021)
This research develops a remote switch notification system by utilizing radio waves. This system will use the RF433 module and RF315 module as the transmission medium, the HT12E module as the encoder and the HT12D module as the decoder. The working principle of the system is that the sending part sends a signal when the voltage is applied via a push button, then the switch is sent to the part of the room and activate the relay. Then in the relay there is also an encoder that will recode the data on the relay that the relay is active and resend the data to false senders so that the LED as notification will turn on. Based on the test results it is known that the remote switch notification system that has been designed is able to turn on and turn off the relay and also be able to transmit the notification properly.